2021
DOI: 10.3389/fmed.2021.772324
|View full text |Cite
|
Sign up to set email alerts
|

A First in Human Trial Implanting Microalgae Shows Safety of Photosynthetic Therapy for the Effective Treatment of Full Thickness Skin Wounds

Abstract: Insufficient oxygen supply represents a relevant issue in several fields of human physiology and medicine. It has been suggested that the implantation of photosynthetic cells can provide oxygen to tissues in the absence of a vascular supply. This approach has been demonstrated to be successful in several in vitro and in vivo models; however, no data is available about their safety in human patients. Here, an early phase-1 clinical trial (ClinicalTrials.gov identifier: NCT03960164, https://clinicaltrials.gov/ct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
44
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 42 publications
(49 citation statements)
references
References 38 publications
1
44
0
Order By: Relevance
“…Although the culture conditions, 30°C and a simple mix medium of mammalian cell culture and algal medium (50:50 mixture), were a compromise for both species, the expression of the hypoxia-inducible factor HIF-1α in the fibroblasts could be reduced by the presence of microalgae. Follow-up studies of this team demonstrated the biocompatibility, safety and potential applicability of microalgae-laden commercial collagen scaffolds for photosynthetic therapies in a mouse full skin defect as well as in a first clinical trial comprising eight patients with full thickness skin wounds ( Schenck et al, 2015 ; Chávez et al, 2016 ; Obaíd et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Although the culture conditions, 30°C and a simple mix medium of mammalian cell culture and algal medium (50:50 mixture), were a compromise for both species, the expression of the hypoxia-inducible factor HIF-1α in the fibroblasts could be reduced by the presence of microalgae. Follow-up studies of this team demonstrated the biocompatibility, safety and potential applicability of microalgae-laden commercial collagen scaffolds for photosynthetic therapies in a mouse full skin defect as well as in a first clinical trial comprising eight patients with full thickness skin wounds ( Schenck et al, 2015 ; Chávez et al, 2016 ; Obaíd et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…This approach has been described by our group in recent in vitro ( Hopfner et al, 2014 ; Centeno-Cerdas et al, 2018 ; Chávez et al, 2021 ) and in vivo ( Schenck et al, 2015 ; Chávez et al, 2016 ) studies, and further confirmed by other independent groups, highlighting its potential application in several medical fields, including tissue engineering and regeneration ( Yamaoka et al, 2012 ; Evron et al, 2015 ; Haraguchi et al, 2017 ; Chen et al, 2020 ), heart ischemia ( Cohen et al, 2017 ), and tumor treatment ( Huo et al, 2020 ; Liu et al, 2020 ; Qiao et al, 2020 ). Moreover, an ongoing clinical trial is confirming its safety for tissue regeneration in humans ( Obaíd et al (2021) accepted for publication. ClinicalTrials.gov Identifier: NCT03960164).…”
Section: Introductionmentioning
confidence: 93%
“…Together these results suggest the clinical translation potential of photosynthetic biomaterials. 105…”
Section: Oxygenation Strategies For Wound Healingmentioning
confidence: 99%